Avaliação do polimorfismo da Ala16ValMnSOD e dos parâmetros bioquímicos no déficit cognitivo na epilepsia - Arend, Josi (2020)
Epilepsy is a chronic neurological condition, characterized by recurrent epileptic seizures that can cause neurochemical, cognitive and psychological changes. The mechanisms of action associated with epilepsy can involve several factors, including inflammatory, oxidative and genetic factors. Studies show that genetic mutations, such as the single nucleotide polymorphism of manganese superoxide dismutase (MnSOD Ala16Val SNP) are associated with some neurological diseases, as well as with the modulation of inflammatory and oxidative pathways. In addition, studies report the involvement of MnSOD Ala16Val SNP in metabolic diseases, such as obesity and dyslipidemia. However, little is known about the relationship between MnSOD Ala16Val polymorphism and epilepsy, as well as the influence of genetic mutation on cognitive, inflammatory, oxidative and glycolipidic parameters. Initially, patients with epilepsy and healthy individuals were recruited to participate in this study. Neuropsychological assessment was performed in both groups using cognitive tests. At first, inflammatory, apoptotic markers and DNA damage were measured in blood samples. Glycolipid parameters were also analyzed, such as serum levels of total cholesterol (CHO), LDL, HDL, triglycerides (TG) and glucose (GLU). The data described in this study revealed that patients with epilepsy, when assessed for cognitive functions, showed impairment in the temporal-spatial orientation, memory, attention, language and executive functions in relation to the control group. In addition, we observed a significant correlation between the duration of epileptic seizures and oral language and problem solving. An increase in depression scores was observed among patients with epilepsy compared to controls. A negative correlation between depression and the temporal-spatial orientation function was found in the patients. Patients also had high levels of TNF-α, IL1β and AChE, as well as an increase in caspase 3 levels (CASP-3) and DNA damage (Picogreen), suggesting the participation of inflammatory and apoptotic pathways in epilepsy. The levels of CHO, LDL, TG and GLU were significantly higher in patients with epilepsy than the control group, whereas in HDL levels, no differences were found between the groups tested. The statistical analysis showed that there was a negative correlation between the levels of total CHO vs. total language; TG vs. semantic verbal memory; TG vs. prospective memory; TG vs. total memory; GLU vs. total attention. Correlations of CHO, LDL, TG, GLU, HDL with other tasks of the neuropsychological test showed no correlations. Regarding the results of the second manuscript, the relationship between the polymorphism of Ala16ValMnSOD with neuropsychological tests was evaluated, as well as with the metabolic, oxidative and inflammatory parameters of patients with epilepsy, compared with healthy controls. Statistical analyzes showed the association of the MnSOD Ala16Val polymorphism with the cognitive deficit, including apraxias, perception, attention, language, executive functions, long-term semantic memories, short-term visual, prospective and total memory in patients with epilepsy with VV genotype in comparison to the control group. Compared to controls and patients with AA and AV genotype, patients with the VV genotype exhibited higher levels of TNF-α, IL-1β, IL-6 and greater activation of CASP -1 and -3 and DNA damage. Our findings also showed a greater activity of the superoxide dismutase (SOD) and acetylcholinesterase (AChE) enzymes in patients with the VV genotype. This study shows a distinct neuropsychological profile between patients with epilepsy and healthy individuals. In addition, the findings suggest that neuropsychiatry alterations can be related to inflammatory, apoptotic pathways and the glycolipid profile. Our results also suggest that the MnSOD Ala16Val polymorphism may be related to the worsening performance of cognitive tests, as well as to the worsening of the inflammatory and oxidative profile, suggesting the influence of genetic factors on the pathophysiology of epilepsy.